PRENATAL DIAGNOSIS OF EXCENCEPHALY : A CASE REPORT - LIKKASIT, Wipaporn (The ASEAN Journal of Radiology, 2023)
Prenatal ultrasonographic diagnosis of 18 weeks gestational age fetus with Exencephaly is reported. Transabdominal ultrasound showed absence of fetal skull with presence of a large volume of brain tissue. The condition is rare and has a lethal outcome. Some authors have called Exencephaly as the variant or precursor of Anencephaly.